Identification of transcriptional regulators encoded by Plasmodium falciparum. - Hoon, Jing Ling. (2009)
Plasmodium falciparum is a eukaryotic parasite that infects humans, causing the disease malaria. Despite advances being made in the understanding of P. falciparum biology in recent years, there are still gaps in our knowledge of P. falciparum transcriptional control, with many transcription factors remaining unidentified. PF14_0633 belongs to the ApiAP2 family, which is postulated to consist of transcription factors. The protein has been shown to bind specific DNA motifs, but its ability to activate transcription remains uncharacterized. To determine whether PF14_0633 is able to activate transcription, vector constructs containing fusions of the GAL4 DNA-binding domain with full-length and truncated PF14_0633 were made. HEK293FT cells were transfected with these constructs, and luciferase reporter assays were carried out to detect for transcription activity. However, no transcriptional activity was detected in all the constructs. Western Blotting revealed that the proteins were not expressed in transfected cells, despite the intact mRNA being detected by RT-PCR. The same problem occurred with GAL4 DBD-pfTBP and GAL4 DBD-pfTFIIB, constructed to test whether plasmodial transcription factors could activate transcription in HEK293FT cells. Thus, in order to be able to determine whether PF14_0633 is a transcription factor, the expression problem of these fusion proteins has to first be solved.